Application of Canvas Business Model in Tourism Objects Kumpe Lake, Cilongok District, Banyumas Regency - Endratno, Hermin; Taufiq, Arif Johar; Rachmawati, Erny (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the study was to design a canvas business model planning idea in the future by looking at the current condition of Kumpe Lake. The analysis tool used was the canvas business model. Data was collected through interviews with informants. The identified elements of the Kumpe Lake canvas business model include:customer segmentnamely local tourists,value propositions.What is offered is Kumpe Lake tourism services and camping areas.Customer relationshipwhat is currently taking place is direct service to tourists;channels used is public mediaon instagram and Website. Key resources, panorama of Kumpe Lake; key activities,includes management of Kumpe Lake and camp area services;key partnerships,local entrepreneurs and levels of society;cost structure,program operating costs, revenue streams comes from entrance ticket revenue and camping equipment rental.